2013
DOI: 10.1097/jnr.0b013e3182829b26
|View full text |Cite
|
Sign up to set email alerts
|

Menarche and Menstruation Through the Eyes of Pubescent Students in Eastern Taiwan

Abstract: In line with previous research, this study shows the need for more individual reproductive health consultations, reliable sex education, and well-planned health policies to assist pubescent students manage menstruation. In addition, this study suggests that the subjugation of girls and women remains a critical issue that must be addressed and challenged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Oftentimes they were discouraged to discuss menstruation at all. This has also been reported in studies conducted with adolescents in Taiwan and Rwanda [ 20 22 ], who similarly reported lack of knowledge on the link between menstruation and ovulation, and reported beliefs such as menstruation being a punishment from the gods, resulting from injury, or that it is a mental or physical ‘disease’. A consequence of this ignorance and secrecy is the maintenance of the stigma surrounding menstruation and menstrual issues.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Oftentimes they were discouraged to discuss menstruation at all. This has also been reported in studies conducted with adolescents in Taiwan and Rwanda [ 20 22 ], who similarly reported lack of knowledge on the link between menstruation and ovulation, and reported beliefs such as menstruation being a punishment from the gods, resulting from injury, or that it is a mental or physical ‘disease’. A consequence of this ignorance and secrecy is the maintenance of the stigma surrounding menstruation and menstrual issues.…”
Section: Discussionsupporting
confidence: 66%
“…In another Indian study based in West Bengal, boys also requested menstruation to be included in the school curriculum [ 23 ] . Chang and colleagues (2013) reported that boys in Taiwan resorted to going online to investigate this topic [ 20 ], as did some of our participants. We wonder therefore, why boys are poorly informed when they could be provided with information that they request, which would serve for their future role as husbands, partners and fathers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, we examined the perception of menarche among members of a particular ethnicity (Korean). Attitudes toward and perceptions of menarche or menstruation have been extensively documented across diverse cultural backgrounds-researchers have examined not only females in Zambia, Nepal, and Hong Kong but also those in Kenya (Secor-Turner, Schmitz, & Benson, 2016), Canada (Rempel & Baumgartner, 2003), Brazil (Makuch, Osis, Petta, De Pádua, & Bahamondes, 2011), Mexico (Marván & Molina-Abolnik, 2012), India (Yagnik, 2012), Taiwan (Chang & Lin, 2013), Jordan (Al Omari et al, 2016), and so on. However, these attitudes and perceptions have not yet been studied in South Korea.…”
Section: Introductionmentioning
confidence: 99%